Pyogenic Granuloma: A Case Report - Maria Jabbar; Hira Butt; Nauman Rauf Khan (Gandhara University, 2021)
Pyogenic granuloma is a type of inflammatory hyperplasia of the oral mucosa and skin that occurs commonly. Histopathologically, it mimics an angiomatous lesion instead of granulomatous disease. These lesions generally appear as a sessile papule or solitary nodule and may have a smooth or lobulated surface clinically. These granulomas present in a variety of sizes, ranging from a few millimeters to several centimeters. About 75% of the pyogenic granulomas of the oral cavity are associated with the gingiva. In this case report a 31 years old female presented in the department of oral and maxillofacial surgery with the complaint of abnormal growth of gingiva in maxillary anterior region. The patient was diagnosed with the pyogenic granuloma (pregnancy tumor), which had developed in the second trimester of her pregnancy. Surgical excision was done to remove the lesion.